Penerapan Antena Mikrostrip di Pesawat Udara Nir Awak (PUNA) Sriti - Guno, Yomi; Hasrito, Eko Syamsuddin (TESLA: Jurnal Teknik Elektro, 2016)
Unmanned aerial vehicle (UAV) in Indonesia is commonly known as Pesawat Udara Nir Awak (PUNA). Data link from aerial observation, required transmitter mounted on the PUNA and components of the constituent is antenna. Antenna must have a small size and light in weight, because the limitation due to the payload capacity. Currently used in the PUNA, is a dipole antenna which still has some weakness, including its susceptibility to the wind (drag effect). So, designing a microstrip antenna will improve the signal transmission performance from PUNA to Ground Control Station (GCS). The microstrip antenna is chosen because this type of antenna has low profile drag, light weight, easy for fabrication and of course low cost. After an antenna design optimization, the antenna placement should be noted to ensure a good transmission. In this research, the microstrip antenna will be operated at 2.35 GHz for video monitoring and the antenna itself will be placed inside the fuselage. Simulated co-site interference will be performed at the operational frequency of data link antenna, which is 900 MHz, with the placement in the upper surface (canopy) of the PUNA. The measurements in the anechoic chamber, showed that the internal fuselage microstrip antenna worked at the frequency of 2.35 GHz with a bandwidth 60 MHz (2.31 GHz up to 2.37 GHz), while the return loss measured at 2.35 GHz is -23.85 dB and the gain of antenna is 3.81 dBi.